An imaginary home in Diana Abu-Jaber's "Arabian Jazz" - Simone Cristina Motta Reis (2015)
This dissertation aims at discussing the changing notions of home, from a locus to an imaginary place for immigrants, specifically Arab Americans. To accomplish this research, I based my research on Diana Abu-Jaber's novel Arabian Jazz to try to demonstrate, through the main characters Matussem, Fatima, Jemorah and Melvina, how each of them represents a phase of diaspora: from classic to contemporary and also their different perspectives of home. With that, I intend to show that the change of the notion of diaspora is connected to the change of the concept of home. I also intend to demonstrate that every diasporic experience is different and unique to each diasporic subject. I will focus this investigation on Jemorah Ramoud and how she copes with her diasporic condition to finally understand what home is.